Pengaruh Model Problem Based Learning terhadap Minat dan Hasil Belajar Matematika Siswa Sekolah Dasar - Aziz Arianto; Muhammadi Muhammadi (Universitas Negeri Padang, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on students’ learning interest and mathematics learning outcomes in elementary school. The research was motivated by the low level of students’ interest and mathematics achievement caused by conventional teacher-centered learning. This study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of fifth-grade elementary school students in Cluster I of Mapat Tunggul Selatan District. The sample was divided into two groups, namely an experimental class taught using the Problem Based Learning model and a control class taught using conventional learning methods. The research instruments included a learning interest questionnaire and a mathematics learning achievement test. Data were analyzed using descriptive and inferential statistics. Since the data did not fully meet the assumptions of normality and homogeneity, hypothesis testing was conducted using the Mann–Whitney U test. The results showed that there were significant differences between the experimental and control classes in terms of both learning interest and mathematics learning outcomes. Students taught using the PBL model demonstrated higher learning interest and better mathematics achievement than students taught through conventional learning. These findings indicate that the Problem Based Learning model has a positive and significant effect on both the affective and cognitive aspects of elementary school students in mathematics learning.